Método Montessori en el desarrollo de Competencias Matemáticas en el cuarto grado de la Escuela “Miguel Riofrío”, Loja 2023-2024 - Ramírez Agila, Jessica Carolina (2024)
The present research work deals with the Montessori Method in the development of mathematical competencies. The general objective was to analyze the incidence of the application of the Montessori method in the development of mathematical competencies of fourth grade students. In order to fulfill this objective, three specific objectives were developed, the first one consisted of: Diagnose the mathematical competencies developed by the students during their learning process, the second was to: To establish a didactic proposal based on the Montessori method for the development of mathematical competencies and the third is: To evaluate the didactic proposal based on the Montessori method for the development of mathematical competencies. The research was based on a mixed approach with descriptive scope and quasi-experimental design, in addition, the deductive and inductive methods were applied, as well as the statistical method, the techniques applied were the interview and pre- and post-evaluative questionnaires for data collection, as well as to diagnose the academic level of mathematical competencies; we worked with non-probabilistic sampling type, representing 17 participants. Based on the results, it is concluded that the implementation of the Montessori method contributes to meaningful learning and the effective development of mathematical competencies such as logical reasoning, problem solving, mathematical communication and modeling, because it motivates the student to be an active constructor of their knowledge through experimentation with concrete material with the Montessori method, being a valuable pedagogical alternative to improve the teaching-learning process of mathematics.